Prospecting the Use of a Virtual Showcase in the Promotion of Collections in Libraries - Vieira, Letycya Cristina Barbosa (2023)
The research aimed to identify the active virtual showcases in the promotion of library collections, investigating the use of the QR Code in the interaction of the virtual and physical environment. A prospective study was carried out on the Computer Program Base of the National Institute of Industrial Property (INPI) and on the information systems: Journal Portal of the Coordination for the Improvement of Higher Education Personnel (Capes), Digital Library of Theses and Dissertations (BDTD), Web of Science, Scopus, IEEE Xplore, ScienceDirect and Scientific Electronic Library Online (Scielo). Most software is from the field of application Marketing (34 citations) from 2019 (19 records) and from legal entities (75.7%). As for the publications, most were found on the Capes Journal Portal (2,091 publications). Virtual showcases have potential in promoting and usability of the collection, but published and/or recorded experiences are almost non-existent, revealing the need to carry out studies in loco to better understand their use.